Investigating a Macro Level Trial Tax: An Analysis of the Relationship Between a Circuit's Plea Proportion and Median Sentence Length in U.S. Federal Courts - LaFontaine, Denise (2019)
This study investigates the relationship between the proportion of cases resolved by plea in the federal court circuits and the median sentence length of those circuits. Through OLS regression, this study models the relationship, controlling for variation in circuits, year, and violent crime proportion. With an understanding of two common theoretical frameworks surrounding the trial tax discussion, this study theorized under a focal concerns perspective that as the proportion of cases resolved by plea in a circuit increases, the median sentence length of that circuit would decrease. The results of this study are consistent with results of prior research showing the existence of a trial tax. Additionally, this study investigates the relationship between the caseload of a circuit and the proportion of cases resolved by plea in a circuit to understand the extent to which caseload influences plea bargaining practices in a circuit. The results of this analysis suggest that caseload differences have little influence on plea proportions when the caseloads are below one hundred. However, caseloads larger than this do tend to be correlated with high plea proportions, supporting the focal concerns theory prediction of increased plea pressure in high caseload courts. Overall, this study provides evidence of a macro level trial tax that is consistent with individual level findings